W poszukiwaniu utraconej metody, czyli Włodzimierz Sołowjow a idea sofijna w nowej książce Henriecke Stahl „Sophia im Denken Vladimir Solov’evs. Eine Ästhetische Rekonstruktion”: In Search of Lost Method, or Vladimir Solovyov and the Sophiological Thought in Henriecke’s Stahl New Book “Sophia im Denken Vladimir Solov’evs. Eine Ästhetische Rekonstruktion” - Kotin, Andriej (Przegląd Wschodnioeuropejski, 2019)
The article is based upon Henriecke Stahl’s newest monograph under the title “Sophia im Denken Vladimir Solov’evs. Eine asthetische Rekonstruktion”. The author’s precise analysis focuses on the metamorphosis of the Sophia-idea in both Solovyov’s philosophy and poetry. The following review discusses the most important aspects of Stahl‘s book as well as the semantic peculiarity of her methodology. Other significant and meaningful elements are various frames of reference between Solovyov and German philosophers (Kant, Hegel, Schelling) and mystics (Jacob Bohme) and Eastern Orthodox thinkers, especially those of the hesychast spiritual tradition (Gregory Palamas, [Pseudo-]Dionisys the Areopagite, Maximus the Confessor).